Apparent digestibility of ruminant rations with increasing levels of concentrates - Ludemann, C. J. F.(Christoph Johannes Friedrich) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc. Agric.) -- University of Stellenbosch, 1970.